Racial variations in tooth pain and care-seeking in adolescents in Malaysia - Kangjie Tay; Cassandra Li Jean Beh; Muneer Gohar Babar; Ting Jing Kweh; Ekta Priya; Allan Pau (Nature Publishing Group, 2021)
Abstract Objective Tooth pain among adolescents is a common event that impacts substantially on quality of life. The purpose of this paper is to explore the role of race in the tooth pain experience and associated care-seeking. Design A cross-sectional questionnaire survey was conducted on 14-18 years from four different public schools in Kuala Lumpur. Socio-demographic, pain symptoms, and social impacts data were collected as well as medication use and visiting a dentist for tooth pain. Results Of 1473 questionnaires distributed, 1452 (98.6%) completed questionnaires were returned, with 269 (18.5%) reported having experienced tooth pain in the past 1 month. Those who identified as Indian (26.1%) were more likely to report tooth pain compared to Chinese (16.5%) and Malay (20.9%). In regression analysis, no factors were identified as independently associated with medication use, but Chinese and Indians compared to Malays, and those expressing difficulty sleeping were more likely to report visiting a dentist for treatment. Conclusion Racial variations in the tooth pain experience and care-seeking have been identified. This may be related to socio-economic status, but further research is needed on the role of culture-related care-seeking and accessibility of dental services.